Public administration employees' readiness and acceptance of e-government: Findings from a Croatian survey. (November 2017) - Dukić, Darko; Dukić, Gordana; Bertović, Neven
Despite the widespread use of digital technology in public administration, little attention has been given to understanding e-government adoption and acceptance by its employees. This paper examines the level of public administration employees' ICT literacy and the extent to which they support e-government. The influence of background variables is also explored in the analysis. A structured online questionnaire was used to gather data from employees of Croatian central government bodies. According to the results, surveyed employees rated their general ICT literacy as high. They are more confident in their basic ICT skills than in advanced ones. The level of such skills is associated with socio-demographic characteristics. The findings also indicate that employees accept e-government, but they are less satisfied with its implementation. However, socio-demographic factors do not affect to a great extent employees' acceptance and satisfaction with e-government. The study expands previous research by analysing the group differences at both manifest and latent levels. It also contributes to the identification of factors that may influence e-government success.